Longitudinal association between neighborhood cohesion and depressive mood in old age: A Japanese prospective study. (July 2015) - Murayama, Hiroshi; Nishi, Mariko; Nofuji, Yu; Matsuo, Eri; Taniguchi, Yu; Amano, Hidenori; Yokoyama, Yuri; Fujiwara, Yoshinori; Shinkai, Shoji
Abstract: Despite increasing evidence of the relationship between neighborhood cohesion and depressive mood, little is known about this longitudinal association in old age. This study examined the association between perceived neighborhood cohesion and depressive mood and the stress-buffering effect of perceived neighborhood cohesion on depressive mood among older Japanese people using the 2010 (baseline) and 2012 (follow-up) Hatoyama Cohort Study datasets. We analyzed 655 participants aged 65–84 at baseline. Although perceived neighborhood cohesion at baseline was not associated with depressive mood at follow-up, high neighborhood cohesion partially offset the deleterious effect of anticipated daily stressors on depressive mood. This effect was stronger for long-term residents of the neighborhood. Interventions to strengthen neighborhood cohesion may help reduce the deleterious effect of stressors on older residents' depressive mood. Highlights: Neighborhood cohesion is not directly associated with depressive mood. Neighborhood cohesion offsets deleterious effects of stressors on depressive mood. This buffering effect is stronger for long-term residents of the neighborhood. Stronger neighborhood cohesion may prevent depressive mood in older Japanese people.